They Got Mad Skills : The Effects of Training on Youth Employability and Resilience to the Ebola Shock - Rosas, Nina; Acevedo, Maria Cecilia; Zaldivar, Samantha (World Bank, Washington, DC, 2017)
This paper discusses a randomized control trial to measure the short-term impacts of a skills intervention among urban youth in Sierra Leone at the onset of the Ebola crisis. The intervention provided (i) technical skills training, plus on-the-job training; (ii) business skills training; and (iii) a mix of (i) and (ii). All groups received stipends and literacy and numeracy training. The findings support evidence that combining cash injections and skills training can stimulate employment and entrepreneurship. The program boosted household consumption and investments in housing and assets, thereby building resilience to the Ebola shock. The effects on cognitive and noncognitive skills were positive and heterogeneous. Youth with greater initial ability experienced more positive labor market and entrepreneurship investment impacts. Youth with less initial ability upgraded skills more extensively, although they channeled benefits into more consumption. These findings emphasize the role of basic safety nets and show that noncognitive tests may improve the targeting of skills interventions in fragile contexts. The results also confirm the age-malleability of noncognitive ability and suggest that, in low-ability contexts, the sensitive years for skill investments may reach into early adulthood.